DASAR-DASAR PENGEMBANGAN KURIKULUM - Yuliani Yuliani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Curriculum development is a process that plans, produces a better tool based on the results of an assessment of the existing curriculum, so as to provide better teaching and learning conditions. In other words, curriculum development is an activity to produce a new curriculum through the steps of curriculum preparation based on the results of assessments carried out during a certain period